Optimum sample size for determining disease severity and defoliation associated with Septoria leaf spot of blueberry - Ojiambo, P.S.; Scherm, H. (Scientific Societies, 2006)
In a 3-year field study, Premier rabbiteye blueberry plants were sampled at three hierarchical levels (leaf, shoot, and bush) to assess severity of Septoria leaf spot (caused by Septoria al- bopunctata) and incidence of defoliation. A positive linear relationship (R2= 0.977, P< 0.0001, n = 2127) was observed between the number of spots per leaf and percent necrotic leaf area, both assessed on individual leaves in mid- to late October. For data summarized at the shoot level, percent defoliation increased nonlinearly (R2= 0.729, P< 0.0001, n= 224) as disease severity increased, with a rapid rise to an upper limit showing little change in defoliation above 60 spots per leaf. Variance components were calculated for disease severity to partition total variation into variation among leaves per shoot, shoots per bush, and bushes within the field. In all cases, leaves per shoot and shoots per bush accounted for >90% of the total variation. Based on the variance components and linear cost functions (which considered the time required to assess each leaf and select new shoots and bushes for assessment), the optimum sample size for assessing disease severity as number of spots per leaf (with an allowable variation of 20% around the mean) was 75 leaves, one each selected from three shoots per bush on 25 bushes (total time required for assessment: 36.1 min). For disease severity expressed as percent necrotic leaf area, the corresponding values were 144 leaves, two each sampled from three shoots per bush on 24 bushes (total time required: 21.7 min). Thus, given the strong correlation between the two disease variables demonstrated in this study, visual assessment of percent necrotic area was the more efficient method. With an allowable variation of 10% around the mean, a sample of 27 shoot from nine bushes was the optimum sample size for assessing defoliation across the 3 years